Financing of The Medium, Small and Micro Enterprises Sector By Sharia Banking: Positive Effects on Economic Growth and Negative Effects on Income Inequality - Purwanto, Purwanto; Fitriyani, Yeny; Lidasan, Datu Mussolini Sinsuat (IKONOMIKA, 2021)
This study aims to find empirical evidence that the financing provided by Islamic banking in Indonesia has a positive effect on economic growth and reduces income inequality. The method used in this study is an analysis of Structural Equation Model PLS using WarpPLS. The analysis shows the empirical evidence that Islamic banking financing of the MSMEs sector has a significant positive effect on economic growth and a significant negative effect on income inequality. Economic growth has also been shown to have a negative effect on inequality. However, the analysis results show that the economic growth is unable to mediate the relationship between financing of the MSMEs sector toward income inequality. This study concludes that financing the MSMEs sector by Islamic banking can increase economic growth in Indonesia and impact reducing people's income. The contribution of this research is that the financing of the MSMEs sector by Islamic banking must be increased because it can increase economic growth and reduce income.